Beitrag zur Entwicklung eines Köders für Wölfe (Canis lupus) zur oralen Vakzination gegen Tollwut - Gräßer, Nora (Tierärztliche Hochschule, 2016)
The purpose of this study was to develop a suitable bait formula which can be used as an oral vaccination bait for wolves (Canis lupus) against rabies. Due to the current population trend of wolfs in Germany an introduction of the zoonosis cannot be ruled out. To guarantee a quick reaction in case of a rabies outbreak the bait matrix in which the blister will be integrated must be machine producible. The development of a suitable bait is necessary to stop or eliminate rabies as has performed in foxes. Therefore the present study has relevancy for animal welfare and conservation. To determine the taste prevalence of wolves different bait combinations were tested in various zoological institutions. The very well accepted intestinal bait (domestic pig) proved to be the optimal positive control and the poorly accepted fish bait (fox bait) served as the negative control in this study. As an egg based bait (egg bait) showed no significant difference in acceptance to the intestinal bait, this was chosen as a base material. In contrast to the intestinal bait the egg bait triggered the necessary chewing movements to perforate the vaccine blister which will be integrated in future. The absolved experiments confirm that the egg bait is suitable for mechanical mass production. Accordingly in this study the egg bait with several flavour enhancing substances and was offered to the wolves. During their main activity time the wolves discovered the egg-rumen-flour-coated bait more significantly often than the egg bait. Thus the egg-rumen-flour-coated bait is the bait of choice. Based on the presented and discussed results future studies can be aimed at finding a suitable blister. It is recommended that the blister is tested by wolves in different institutions. The final step would then be to test the reaction of free ranging wolves to the whole bait (matrix + blister) in the field. Ziel dieser Studie war es, eine geeignete Köderformulierung zu entwickeln, die in Zukunft als oraler Impfköder für Wölfe (Canis lupus) eingesetzt ...